An outbreak of infection due to severe acute respiratory corona virus-2 in a neonatal unit from a low and middle income setting - Nakwa, Firdose Lambey; Thomas, Reenu; van Kwawegen, Alison; Ntuli, Nandi; Seake, Karabo; Kesting, Samantha Jane; Kamanga, Noela Holo Bertha; Kgwadi, Dikeledi Maureen; Chami, Neema; Mogajane, Tshiamo; Ondongo-Ezhet, Claude; Maphosa, Thulisile Nelly; et al. (Frontiers in Pediatrics, 2022)
Introduction: Provision of kangaroo mother care (KMC) involving continuous skin-to-skin care (SSC) is an important intervention in neonatal care, including being recommended when women are infected with severe acute respiratory syndrome coronavirus (SARS-CoV-2). We report on a nosocomial outbreak of SARS-CoV-2 infections in a KMC ward. Methods: Contact tracing was conducted following diagnosis of SARS-CoV-2 in a mother lodging in the KMC ward. All mother-newborn dyads in KMC and healthcare workers (HCW) were tested for SARS-CoV-2 within 24 - 72 hours of diagnosing the index case. Nasopharyngeal swab samples were obtained and tested from contacts, with a nucleic acid amplification test (NAAT) assay. Next generation sequencing was done on positive samples. Secondary attack rate (SAR) was calculated assuming that the mother who presented with symptoms was the source of infection. Results: Twelve (70.6%) of 17 mothers and 8 (42.1%) of 19 neonates who were in the KMC ward with the index case, were found to be positive with SARS-CoV-2. Seven (87.5%) of the 8 positive neonates had mothers that tested positive. Seventy-five percent (9/12) of the positive mothers and 62.5% (5/8) of the positive neonates were asymptomatic. Eight (27.6%) of 29 HCW were found to be positive and were all asymptomatic. One neonate died from Acinetobacter baumannii sepsis, and his post-mortem lung histopathology showed features compatible with SARS-CoV-2 pneumonia. The sequencing of 13 specimens, which included 1 mother-newborn dyad indicated clustering to the same phylogenetic lineage with identical mutations. In assessing for factors contributing to this outbreak, it was found that spaces between beds were less than one meter and mothers had their meals around the same table at the same time. Conclusion: We report on nosocomial outbreak of SARS-CoV-2 in a KMC ward, affecting a high number of mothers and neonates, and to a lesser extent HCW. Though it is difficult to point to the index case as the source of this outbreak, as asymptomatic individuals can spread infection, inadequate adherence to non-pharmaceutical interventions was assessed to have contributed to the spread of infection. This highlights the need for awareness and adherence to mitigation strategies to avoid SARS-CoV-2 outbreaks